AI-powered commerce : building the products and services of the future with commerce. AI - Pandharikar, Andy; Bussler, Frederik (Packt Publishing, 2023)
Learn how to use artificial intelligence for product and service innovation, including the diverse use cases of Commerce. AI About This Audiobook Learn how to integrate data and AI in your innovation workflows Unlock insights into how various industries are using AI for innovation Apply your knowledge to real innovation use cases like product strategy and market intelligence In Detail Commerce. AI is a suite of artificial intelligence (AI) tools, trained on over a trillion data points, to help businesses build next-gen products and services. If you want to be the best business on the block, using AI is a must. Developers and analysts working with AI will be able to put their knowledge to work with this practical guide. You'll begin by learning the core themes of new product and service innovation, including how to identify market opportunities, come up with ideas, and predict trends. With plenty of use cases as reference, you'll learn how to apply AI for innovation, both programmatically and with Commerce. AI. You'll also find out how to analyze product and service data with tools such as GPT-J, Python pandas, Prophet, and TextBlob. As you progress, you'll explore the evolution of commerce in AI, including how top businesses today are using AI. You'll learn how Commerce. AI merges machine learning, product expertise, and big data to help businesses make more accurate decisions. Finally, you'll use the Commerce. AI suite for product ideation and analyzing market trends. By the end of this artificial intelligence audiobook, you'll be able to strategize new product opportunities by using AI, and also have an understanding of how to use Commerce. AI for product ideation, trend analysis, and predictions. Audience This AI audiobook is for AI developers, data scientists, data product managers, analysts, and consumer insights professionals. The audiobook will guide you through the process of product and service innovation, no matter your pre-existing skillset.